Sustainability of pneumococcal conjugate vaccination in Ghana: a cost-effectiveness analysis in the context of donor transition - Abdul-Mumin Ibrahim; Richmond Owusu; Justice Nonvignon (Frontiers Media S.A., 2024)
BackgroundStreptococcus pneumonia is responsible for 18% of infant deaths in Ghana. With co-financing from Gavi in 2012, Ghana introduced the PCV13 into the childhood immunization programme to reduce the burden of Streptococcus pneumonia. However, Ghana will graduate to the Gavi fully self-financing phase in 2026, when the nation assumes full responsibility of paying for the PCV13. This research aims to evaluate the health impact and cost-effectiveness of PCV13 immunization in Ghana since its implementation and after the cessation of support from Gavi.MethodsWe used the UNIVAC tool to evaluate two main scenarios of cost-effectiveness, from vaccine introduction (2012-2025) and after Gavi transition (2026-2031) in comparison with no vaccination. The sources of data include national data, international estimates and expert opinion. Cost was considered from both the government and societal perspectives. We discounted health outcomes at 3%. Currency values were stated in US Dollars. We tested the robustness of the base case results by performing scenario and sensitivity analyses.ResultsPCV13 will reduce the pneumococcal disease burden by 48% from 2012 to 2031. The vaccination programme costs are USD 130 million and USD 275 million in 2012-2025 and 2026-2031 respectively. It also has a budget impact of USD 280 million for the 2026-2031 period from the perspective of government. The incremental cost-effectiveness ratios are USD 89 and USD 73 respectively from the perspectives of government and society in 2012-2025. The incremental cost-effectiveness ratios are USD 530 and USD 510 respectively from the perspectives of government and society in 2026-2031.ConclusionThe PCV13 vaccination programme in Ghana is cost-effective at 50% GDP per capita threshold even when Gavi withdraws co-financing support from 2026 onwards.